1999
DOI: 10.1007/bf02469876
|View full text |Cite
|
Sign up to set email alerts
|

Structural materials for atomic reactors with liquid metal heat-transfer agents in the form of lead or lead—Bismuth alloy

Abstract: Natural safety nuclear reactors operate at a working temperature of the liquid-metal lead heat-transfer agent equal to 550~ which intensifies the metal corrosion and is fraught with the danger of thermal embrittlement. It is shown that long-term operation of the equipment requires inhibition of the heat-transfer agent by oxygen and the use of silicon steels. However, alloying with silicon increases the susceptibility of the steel to thermal and radiative embrittlement. This makes it necessary to create new ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 2 publications
2
29
0
Order By: Relevance
“…Weeks and Klamut [12] emphasised that the driving force for the dissolution is the temperature dependence of the solubility of the solid metal in the liquid eutectic. Gorynin et al [1] determined that, for oxygen concentrations lower than 5 · 10 À8 wt%, the austenitic stainless steels undergo in lead at 550°C a dissolution process, whereas at higher oxygen concentrations oxidation occurs preventing dissolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weeks and Klamut [12] emphasised that the driving force for the dissolution is the temperature dependence of the solubility of the solid metal in the liquid eutectic. Gorynin et al [1] determined that, for oxygen concentrations lower than 5 · 10 À8 wt%, the austenitic stainless steels undergo in lead at 550°C a dissolution process, whereas at higher oxygen concentrations oxidation occurs preventing dissolution.…”
Section: Discussionmentioning
confidence: 99%
“…It is accepted that austenitic steels may be used in contact with liquid lead-bismuth if the region of operating temperatures is not beyond 400°C. For higher temperatures, martensitic steels are recommended [1]. However, long operation times leads to the dissolution of some elements of the steel (Ni, Cr and Fe, mainly) in the liquid metal and hence some method of protection is needed.…”
Section: Introductionmentioning
confidence: 98%
“…(b) to protect the steel surface by coating or alloying it [5] or by an Ôin situ passive oxidationÕ [6,7]. However, as the phenomena affecting the interactions between a liquid metallic material and a solid substrate depend strongly on the particular system and on the operating conditions, specific investigations have to be performed, helping the compatibility behaviour between the materials to be understood.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore ferritic, ferritic-martensitic (F/M) and oxide dispersion-strengthened (ODS) alloys are better candidates for such applications. It has been shown that the addition of aluminum to the Fe-based ferritic materials is beneficial in preventing corrosion attack and severe oxidation, by forming an Al-rich oxide layer [29][30][31][32][33][34] Generally, the higher the Cr content present, the lower the Al content that is acceptable. Fe-Cr-Al 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 4 alloys display a so-called 'third element effect' (TEE), where Cr (having an oxygen affinity intermediate between those of Fe and Al) is supposed to induce a transition between the internal and external oxidation of Al on ternary alloys under lower Al levels than for binary Fe-Al alloys [37][38][39].…”
Section: Introductionmentioning
confidence: 99%